7(3x+6)=7-(x-2)

Simple and best practice solution for 7(3x+6)=7-(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(3x+6)=7-(x-2) equation:


Simplifying
7(3x + 6) = 7 + -1(x + -2)

Reorder the terms:
7(6 + 3x) = 7 + -1(x + -2)
(6 * 7 + 3x * 7) = 7 + -1(x + -2)
(42 + 21x) = 7 + -1(x + -2)

Reorder the terms:
42 + 21x = 7 + -1(-2 + x)
42 + 21x = 7 + (-2 * -1 + x * -1)
42 + 21x = 7 + (2 + -1x)

Combine like terms: 7 + 2 = 9
42 + 21x = 9 + -1x

Solving
42 + 21x = 9 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
42 + 21x + x = 9 + -1x + x

Combine like terms: 21x + x = 22x
42 + 22x = 9 + -1x + x

Combine like terms: -1x + x = 0
42 + 22x = 9 + 0
42 + 22x = 9

Add '-42' to each side of the equation.
42 + -42 + 22x = 9 + -42

Combine like terms: 42 + -42 = 0
0 + 22x = 9 + -42
22x = 9 + -42

Combine like terms: 9 + -42 = -33
22x = -33

Divide each side by '22'.
x = -1.5

Simplifying
x = -1.5

See similar equations:

| 8(v+2)-4v=2(2v+1)-4 | | y=41/11(20)+128/11 | | -6m-6+8m=-5m-5+2m-1 | | y=41/11(18)+128/11 | | 3=4p+8-3p | | -30=5r | | (y-4)(3-7)=.25 | | 3c+5=2c+2 | | 67x-34+2=5 | | 8(v+2)-4v+7=8v+7 | | 3+(56+x)=34 | | 21j-12=14j+37 | | -6y+14+14y=32 | | 7=-d+13 | | -21.2=p-12.7 | | .333h-4(.666h-3)=.666h-6 | | 8-5n=-7 | | 18a^6-25a^5+8a^4=0 | | 4n+12=2 | | 4x-2/3=x+2 | | 4s-1=8-2a | | -(3x-5)=2 | | 35y^4-205y^3+150y^2=0 | | y-7=-4x-4 | | (9y^2)-12y+1=0 | | 2x^4-24x^3+54x^2=0 | | 6m=8-9-6m | | 5t-3=8t-12 | | 2r+8-1=-3 | | 6h+4g=77 | | -x-2x=-8 | | (4y^2)+7=12y |

Equations solver categories